Design of an Android-Based Mobile Application for Nutritional Consultation and Status Monitoring - Rizaldy, Al Haydar; Fachrie, Muhammad; Ikrimach (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Access to and awareness of nutritional health services in Indonesia play a crucial role in preventing various diseases in children and adults. This study develops an Android-based application aimed at enhancing access to nutritional information and consultation services, as well as promoting effective nutritional management methods. The application was developed using the Waterfall methodology, encompassing stages of requirements analysis, design, implementation, testing, and maintenance, to ensure that the resulting application meets the specified requirements and provides optimal solutions for nutritional consultation and monitoring. The application is designed to meet the needs of users and nutrition experts through features such as registration, consultation, and a Body Mass Index (BMI) calculator. Developed using Android Studio, MySQL, and XAMPP, the application was tested on various Android devices and demonstrated stable and smooth performance. Ongoing maintenance is implemented to ensure continuous optimal functionality. The application also features the selection of nutrition experts according to user preferences and a BMI calculator that allows users to independently check their nutritional status. Compatible with Android Oreo and later versions, the application requires an internet connection to optimize all functionalities, including consultation services and content updates. This application is expected to improve accessibility and individual awareness of nutritional health services in Indonesia.